DISPARITAS DAN KONVERGENSI PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PER KAPITA ANTAR KABUPATEN/ KOTA DI PROVINSI BALI - Savitri Gama, Ayu (INPUT Jurnal Ekonomi dan Sosial, 2009)
This research is aimed at analyzing regional disparity among regencies in Bali Province from 1993 up to 2006.Williamson’s weighted coefficient of variation is used to measure the regional disparity in Bali. Besides of regionaldisparity, this research has identified the convergence or divergence of PDRB per individual person, and also anyfactors that have been influencing the regional disparity and convergence.The result of analyzes indicates that there is an increasing regional disparity among regencies in Bali during1993-2006. Many factors caused disparity are Lag PDRB Per Capyta, Investment Allocation, human capital, andemployer. From the result of pooled data estimation, the Investment allocation influences the regional convergence.